2011
DOI: 10.33073/pjm-2011-007
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Adaptation of Saccharomyces cerevisae to Increased Ethanol Tolerance and Production

Abstract: A total of 24 yeast strains were tested for their capacity to produce ethanol, and of these, 8 were characterized by the best ethanol yields (73.11-8 1.78%). The most active mutant Saccharomyce s cerevisiae ER-A, resistant to ethanol stress, was characterized by high resistance to acidic (pH 1.0 and 2.0), oxidative (1 and 2% of H2O2), and high temperature (45 and 52 degrees C) stresses. During cultivation under all stress conditions, the mutants showed a considerably increased viability ranging widely from abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Viable cell counts of UVNR56 were significantly higher than the wild-type, but its viability was lower compared to the no added ethanol conditions (Figure 2 b). Several studies have shown that an improvement in ethanol tolerance leads to an increase in both ethanol productivity and yield (Basso et al 2008 ; Fiedurek et al 2011 ; Hou 2009 ). As expected, we found a correlation between cell viability and fermentation capability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viable cell counts of UVNR56 were significantly higher than the wild-type, but its viability was lower compared to the no added ethanol conditions (Figure 2 b). Several studies have shown that an improvement in ethanol tolerance leads to an increase in both ethanol productivity and yield (Basso et al 2008 ; Fiedurek et al 2011 ; Hou 2009 ). As expected, we found a correlation between cell viability and fermentation capability.…”
Section: Resultsmentioning
confidence: 99%
“…In the ethanol industry, ethanol production is usually among 10-14% (v/v) and the theoretical yield has to be as high as 90-93% of the fermentation efficiency for the conversion of glucose into ethanol (Bai et al 2008 ). Consequently, several studies to date have focused interest on ethanol tolerance of ethanol-producing yeasts based on the presumption that ethanol-tolerant yeast strains would have enhanced ethanol productivities and yields (Fiedurek et al 2011 : Shi et al 2009 ; Thammasittirong et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae strain ER‐A reached an ethanol concentration of 80 g/L, ethanol productivity of 1.1 g/L/h, and ethanol yield (% of theoretical) of 99.26, which were significantly higher in comparison with the parent strain (ethanol concentration 58 g/L and productivity of 0.8 g/L/h). The studies seem to confirm a highly effective selection of yeast strains resistant to high ethanol concentrations by adaptation .…”
Section: Introductionmentioning
confidence: 57%
“…Considerably increased viability occurred in mutants during cultivation under all stress conditions, the level of which ranged widely from about 1.04 to 3.94‐fold in comparison with the parent strain S . cerevisiae ER .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation